Multiple Nanosheets Assembled Nanoflower‐like MnO2 to Anchor Polysulfides for Improving Electrochemical Performance in Lithium Sulfur Batteries. Issue 24 (24th June 2019) - Wang, Jianing; Li, Yanpei; Li, Wenwen; Sun, Changzhi; Qi, Congyu; Jin, Jun; Wen, Zhaoyin
Abstract: Lithium sulfur batteries hold great promise as the new generation post‐lithium‐ion batteries in virtue of high theoretical energy density (2600 W h/kg) and low cost of sulfur. However, the practical application of the batteries is being hindered by their poor cycling stability and low Coulombic efficiency, which is mainly attributed by the dissolution of polysulfides and low electronic conductivity of sulfur. Herein, a novel cathode host was designed by mixing the nanoflower‐like MnO2 with KB powder loaded on the commercial carbon paper, delivering excellent electrochemical performance even at a high sulfur mass loading of 2.1 mg/cm 2 . The nanoflower‐like MnO2 obtained from the typical hydrothermal method provides abundant active sites for adsorbing polysulfides chemically. The combination between this chemical capture effect and physical constraint introduced by the pores of nanoflower‐like MnO2 and KB powder suppresses the dissolution of lithium polysulfides out of cathode region. Consequently, the modified MnO2 ‐KB@carbon paper‐Li2 S6 cathode exhibits an initial discharge capacity of 776.4 mAh/g at 0.5 C and retain 814.3 mAh/g after 100 cycles with nearly 100% Coulombic efficiency. Remarkably, self‐discharge rate has been restrained to a very level of 4.7% after 48 h resting, indicating the potential of the nanoflower‐like MnO2 ‐KB@carbon paper‐Li2 S6 cathode for improved preserving ability of lithium sulfur battery. Abstract : A novel cathode host was synthesized by mixing the nanoflower‐like MnO2 with KB powder loaded on the commercial carbon paper, exhibiting excellent electrochemical performance even at a high sulfur mass loading of 2.1 mg/cm 2 . Remarkably, self‐discharge rate has been restrained to a very level of 4.7% after 48 h resting, indicating the potential of the nanoflower‐like MnO2 ‐KB@carbon paper‐Li2 S6 cathode for improved preserving ability of lithium sulfur battery.